Allelopathy: the potential of medicinal plants in the control of spontaneous species - Giardini Bonfim, Filipe Pereira [UNESP]; Torres Menezes, Gabriela Machado [UNESP]; Oliveira Gomes, Jordany Aparecida de [UNESP]; Teixeira, Daniela Aparecida [UNESP]; Solano Mendoza, Juan David [UNESP]; Parreiras, Nathalia de Souza [UNESP] (Univ Central Marta Abreu Las Villas, 2018)
As an option for the problem of agrotoxics, agroecology has sought the control of spontaneous species through the use of parts of plants with herbicidal activity. The following work consists of a bibliographical research that aims to gather the information disseminated in several articles on the biodiversity of medicinal plants as natural herbicides. For the review of the literature, it was decided to search for articles in national and international journals during the period from 1997 to 2014. Several studies that cover medicinal plants were observed in the literature, but the evaluation of allelopathic potential is limited. The study added medicinal plants that possess potential secondary allelopathic compounds, with the possibility of being used in the production of natural herbicides. It is important to encourage this type of studies, for an ecological perspective in general, to enable the manipulation of allelopathic interactions related to agriculture.
Keywords: agroecology; allelopathy; natural herbicides; medicinal plants